2021
DOI: 10.1002/jmv.27539
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the polybasic furin cleavage site of spike protein in SARS‐CoV‐2 replication, pathogenesis, and host immune responses and vaccination

Abstract: The polybasic furin cleavage site insertion with four amino acid motifs (PRRA) in spike protein's S1/S2 junction site is important in determining viral infectivity, transmission, and host range. However, there is no review so far explaining the effect of the furin cleavage site of the spike protein on SARS-CoV-2 replication and pathogenesis in the host and immune responses and vaccination. Therefore, here we specifically focused on genomic evolution and properties of the cleavage site of spike protein in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Moreover, the risk of reinfection of previously COVID‐19 infected patients with the Omicron variant is very evident, indicating higher transmissibility 15 . Omicron variant mutations H655Y and N679K are present near the furin cleavage site (FCS) and can increase spike cleavage, making the virus more contagious 27,28 . On the other hand, P681H can multiply transmissibility by increasing the spike protein cleavage 29 …”
Section: Transmissibility Of Omicron Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the risk of reinfection of previously COVID‐19 infected patients with the Omicron variant is very evident, indicating higher transmissibility 15 . Omicron variant mutations H655Y and N679K are present near the furin cleavage site (FCS) and can increase spike cleavage, making the virus more contagious 27,28 . On the other hand, P681H can multiply transmissibility by increasing the spike protein cleavage 29 …”
Section: Transmissibility Of Omicron Variantmentioning
confidence: 99%
“…15 Omicron variant mutations H655Y and N679K are present near the furin cleavage site (FCS) and can increase spike cleavage, making the virus more contagious. 27,28 On the other hand, P681H can multiply transmissibility by increasing the spike protein cleavage. 29 Furthermore, the new variant Omicron gives a false negative result in polymerase chain reaction tests because of the "S gene target failure," which paves the way of spreading the infection at a higher speed worldwide.…”
Section: Transmissibility Of Omicron Variantmentioning
confidence: 99%
“… 5 , 24 S1/S2 cleavage site mutations H655Y, N679K, and P681H result in increased S1/S2 furin cleavage and facilitate efficient viral entry into the host. 25 While, S477N, Q498R, and N501Y mutations affect the ACE‐2 binding affinity, S477N and E484A are responsible for immune evasion. 20 , 26 Further, K317T/N, L452R, Y453F, S477N, E484K, and N501Y mutations were shown to evade neutralization by 11 of the 13 analyzed monoclonal antibodies (mAbs).…”
Section: Mutational Landscape Of Omicron Variantmentioning
confidence: 99%
“… 36 However, it was recently demonstrated that additional (booster) mRNA vaccine doses may help to improve anti‐viral antibody responses against new SARS‐CoV‐2 variants. 135 …”
Section: Mutations In Sars‐cov‐2 Variantsmentioning
confidence: 99%